Improvement of soft soil stiffness using geo-composite cellular mat - Tuan Ismail, Tuan Noor Hasanah; Wijeyesekera, Devapriya Chitra; Mohd Yusoff, Aima Nadia; Lim Meng Siang, Alvin John (Penerbit Uthm, 2018)
The highway construction over sub-grade consisting of problematic soils gives challenges to the engineer due to their weak geotechnical characteristic [1, 2, 3];  High water content,  High compressibility, and  Low bearing capacity.